Acumulación en ejecución de garantías tras la modificación de los Procesos Únicos de Ejecución - Vilela Carbajal, Karla (Revista de Derecho, 2019)
The article analyzes two postulations which might be presented in n enforcement of security process, both related to accumulation: 1) If an individual lends a sum of money to another individual, the latter appoints two or more people as guarantors, each of whom guarantees the obligation with a mortgage; and 2) If an individual lends a sum of money to another individual, who offers the mortgage of two or morePrior to the analysis of both postulates two previous matters are studied: accumulation in the CPC and the enforcement of security. As regards accumulation, its concept, types and requisites are clarified. As regards the study of enforcement of security the problems around the required executive title in an enforcement of security are analyzed. The postulates which are object of the present study are analyzed under the new normative, since 2008, which moves around the so-called single process executions, and specifically to the norms related to enforcement of securities.